Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.

Metal halide structure and the extent of distortion control the photo-physical properties of luminescent zero dimensional organic-antimony(iii) halide hybrids - Biswas, Anupam; Bakthavatsalam, Rangarajan; Mali, Bhupendra P.; Bahadur, Vir; Biswas, Chinmoy; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Antimony(iii) halide based zero dimensional hybrids have gained attention as broadband emitters. Until now, quadrangular pyramidal SbX5 based and octahedral SbX6 based 0D hybrids have been reported utilizing different organic ligands demonstrating some structural tunability affecting their emissive properties. Utilizing a common organic ligand, here we demonstrate the structural tunability (quadrangular pyramidal, octahedral, or a combination thereof) of the metal halide unit in Sb(iii)Cl 0D hybrids with contrasting photo-physical properties (broadband, Stokes shift, strong/weak colored emission). The structure-property-mechanism correlation of the synthesized compounds [1 (C12H52Cl18N8O4Sb3; tris Sb green); 2 (C12H50Cl14N8O3Sb2; tris Sb red); 3 (C24H88Cl25N16O4Sb3; tris Sb yellow)] identifies crucial factors that control their emissive properties. The X-ray analysis reveals the structure (1-octahedral; 2-quadrangular pyramidal; 3-combination thereof) and the order of the extent of structural distortion as 1-3 MUCH LESS-THAN 2. The metal halide coordination environment asymmetry and its structure are observed to dictate PL emission energy (1-green; 2-red; 3-yellow) as supported by a qualitative Molecular Orbital scheme. The extent of structural distortion guides the observed Stokes shifts (1-165 nm; 2-290 nm; 3-200 nm; 1-3 < 2). Interestingly, the extent of distortion is found to be well correlated with the observed PLQY (1-45%; 2-6%; 3-43%; 1-3 >> 2). This report clearly demonstrates the structural tunability and the effect of the metal halide unit structure/distortion in shaping the emissive properties of 0D organic Sb(iii) halide hybrids.

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Controlled modulation of the structure and luminescence properties of zero-dimensional manganese halide hybrids through structure-directing metal-ion (Cd2+ and Zn2+) centers - Das, Deep Kumar; Bakthavatsalam, Rangarajan; Anilkumar, Vishnu; Mali, Bhupendra P.; Ahmed, Md Soif; Raavi, Sai Santosh Kumar; Pallepogu, Raghavaiah; Kundu, Janardan (Inorganic Chemistry, 2022)
Zero-dimensional (0D) metal halide hybrids with high exciton binding energy are excellent materials for lighting applications. Controlling/modulating the structure of the con-stituent metal halide units allows tunability of their photo-luminescence properties. 0D manganese halide hybrids are currently attracting research efforts in lighting applications due to their eco-friendly and strong emission. However, structural transformation-induced tunability of their photophysical propertieshas rarely been reported. Herein, we demonstrate a rationalsynthetic strategy to modulate the structure and luminescenceproperties of 0D Mn(II) halide hybrids utilizing the structure-directing d10metal ions (Cd2+/Zn2+). 0D metal halide hybrids ofCd2+/Zn2+, which act as hosts with tunable structures, accept Mn2+ions as substitutional dopants. This structural flexibility of thehost d10metal ions is realized by optimizing the metal-to-ligand ratio (Cd/AEPip). This reaction parameter allows structuraltransformation from an octahedral (AEPipCdMnBrOh) to a tetrahedral (AEPipCdMnBrTd) 0D Mn halide hybrid with tunableluminescence (orange -> green) with high photoluminescence quantum yield. Interestingly, when Zn2+is utilized, a tetrahedralAEPipZnMnBr structure forms exclusively with strong green emission. Optical and single-crystal X-ray diffraction structural analysisof the host and the doped system supports our experimental data and confirms the structure-directing role played by Cd2+/Zn2+centers. This work demonstrates a rational strategy to modulate the structure/luminescence properties of 0D Mn(II) halide hybrids, which can further be implemented for other 0D metal halide hybrids